2019
DOI: 10.3390/ijms20215322
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between MicroRNAs and Oxidative Stress in Ovarian Conditions with a Focus on Ovarian Cancer and Endometriosis

Abstract: Ovarian cancer and endometriosis are two distinct gynaecological conditions that share many biological aspects incuding proliferation, invasion of surrounding tissue, inflammation, inhibition of apoptosis, deregulation of angiogenesis and the ability to spread at a distance. miRNAs are small non-coding RNAs (19-22 nt) that act as post-transcriptional modulators of gene expression and are involved in several of the aforementioned processes. In addition, a growing body of evidence supports the contribution of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 159 publications
(182 reference statements)
0
21
0
Order By: Relevance
“…Brucella, Chlamydia, and Mycoplasma have been detected in over 60% of samples from those with EOC, and it is thought that the microbial dysbiosis may contribute to development of atypical epithelial cells showing hyperplasia and cytological atypia. These changes, along with genetic mutations in the ovaries gradually progress to EOC cells, particularly endometrioid and clear cell types (44)(45)(46). Figure 1 illustrates the potential carcinogenic mechanisms involved in the development of EOVC.…”
Section: Microbial Communities In Female Reproductive Tractmentioning
confidence: 99%
“…Brucella, Chlamydia, and Mycoplasma have been detected in over 60% of samples from those with EOC, and it is thought that the microbial dysbiosis may contribute to development of atypical epithelial cells showing hyperplasia and cytological atypia. These changes, along with genetic mutations in the ovaries gradually progress to EOC cells, particularly endometrioid and clear cell types (44)(45)(46). Figure 1 illustrates the potential carcinogenic mechanisms involved in the development of EOVC.…”
Section: Microbial Communities In Female Reproductive Tractmentioning
confidence: 99%
“…Endometriosis is a disease characterized by ectopic growth of endometrial tissue, resulting in pain symptoms and reduced fertility in affected patients [ 100 ]. MicroRNA expression is dysregulated in endometriosis and has been functionally linked to invasive growth, aberrant proliferation and stem cell function [ 101 , 102 , 103 , 104 ]. MicroRNA let-7d-3p is significantly downregulated in women with endometriosis [ 105 ].…”
Section: Let-7d In Endometriosismentioning
confidence: 99%
“…However, there has been no data on whether EAOC has a strong ability to resist oxidative stress, and there is no evidence to support this hypothesis. In addition, it has recently been reported that the interaction between oxidative stress and non-coding microRNAs has an important role in the development of EAOC [ 19 ], but further study is required.…”
Section: Endometriosis and Eaocmentioning
confidence: 99%